Predicting the potential geographic distribution of Thrips palmi in Korea, using the CLIMEX model. Issue 2 (9th April 2014) - Park, Jung‐Joon; Mo, Hyoung‐ho; Lee, Gwan‐Seok; Lee, Sung‐Eun; Lee, Joon‐Ho; Cho, Kijong
Abstract Thrips palmi Karny, melon thrips was introduced and first recorded in 1993 in Korea. This species has become a serious pest of vegetable and ornamental crops. The CLIMEX simulation was applied to T. palmi to predict its potential geographic distribution in Korea under the Representative Concentration Pathway (RCP) 8.5 climate change scenario. In the CLIMEX simulation, the ecoclimatic index was calculated, and compared in each simulated year and each simulated location. The map comparisons show good agreements between simulated and present distributions of T. palmi, indicating that the CLIMEX model has promising potential for prediction of future distributions of this species in Korea. In the near future, until the year 2020, all the western and eastern parts of Korea show favorable to marginal suitability for T. palmi populations in the fields. After the year 2040, potential distributions shift from no persistence to favorable for establishment and persistence from coastal to interior regions of the Korean peninsula, except for a north‐eastern interior region which is the northernmost part of a high mountainous (Baekdu‐Daegan) area in Korea. Based on the simulation results, the geographical distribution of T. palmi will expand over its current weather restrictions in the near future under a severe climate change scenario. Thus, pest management measures and strategies should be re‐evaluated in Korea, and should include further studies on interspecific competition and ecosystem changes due to climate changes.